Sustentabilidade, complexidade e economia: dinâmicas e perspectivas - Camargo, Jhean Steffan Martines de (Universidade Federal de São Carlos, 2018)
In the 1960s, the environmental debate took shape with the publication of two classics: Rachel Carlson's Silent Spring and Paul Ehrlich's The Population Bomb. The debate itself challenged the manner in which industrial capitalism acted in ways that caused the killing of other animal species in ways that undermined the fragile ecological that kept the relationship between man and the natural environment stable. Thus, the separation of the phenomena that cause the environmental disturbances of human action in relation to the nature of the harmful effects of animal mortality or the depletion of renewable resources, living or not, is under suspicion. In this text, the object of study is to observe in a logical line the perception of what is environmental collapse, from the analysis of bibliographical references, whose objective is to contextualize in the present how the action of man in the remote past in the history of the Mediterranean caused a environmental collapse that almost led to a food shortage collapse situation. In the same way, we seek to base on theoretical components the explanation versed within the interdisciplinarity between economics, ecology, and physics, in the light of complexity theory. From the results found, one can see an approximation of complexity theory with classical texts such as The Population Bomb or Our Common Future Report, or the Brudtland Report, similarly, by conducting an investigation into environmental indicators such as EPI. (Environmental Performance Index), it is clear that there is a strong convergence between the indicators of economic complexity (ECI) and the EPI.
Sustainability, complexity and economy: dynamics and Perspectives
Keywords: Ecologia. Economia. Recursos Naturais. Sistemas Complexos. Complexidade. Economia Ecológica. Ecology. Economy. Natural resources. Complex Systems. Complexity. Ecological Economics; CIENCIAS EXATAS E DA TERRA; CIENCIAS HUMANAS; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA APLICADA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS; OUTROS::CIENCIAS ATUARIAIS